The Assessment of Internal Control System in Management of Information Technology Based on COSO IC - Fadlan, Muhammad; Winarno, Wing Wahyu; Haryono, Kholid; -, Muhammad (Sekolah Tinggi Teknologi Adisutjipto, 2018)
The large number of institutions that use information technology (IT) to help run their usiness processes cannot be separated from various risks to IT. The internal control system is one way that can be used to deal with and even minimize the impact of various risks and COSO Internal Control is one of the frameworks that can be used. The